Культура польско-восточнославянского пограничья в аспекте мезонимии - Mironiuk, Leontij (Acta Polono-Ruthenica, 2008)
The article studies certain phenomena of a cultural borderland, mezonimy and intertexualitytaken in relation. The author classifies these in two aspects: a) due to the function - a resonancespace of a text / literature; b) due to the place - mezonimic spheres in structure. Special attentionwas paid to excerpts of Pushkin’s texts translated by Julian Tuwim, Adam Ważyk and Maxim Rylski.The author examines some Russian and Polish eponyms as well as pro-drop parameter phenomenonin Polish and Ukrainian languages.